MARKETING & DISTRIBUTION OF HUL: ITS RURAL ORIENTATION - Rajani, N. Sree; Reddy, V. Bhargavi (International Journal of Research -GRANTHAALAYAH, 2017)
Hindustan Unilever Limited (HUL), formerly known as Hindustan Lever Limited (HLL), is the largest consumer products company in India. The name HUL came into vogue in late June 2007. The Head office of the company is located in Mumbai. There are in all 41,000 employees of different categories working in the company. The company is headed by a non-executive Chairman (presently Mr. Hareesh Manwani. HUL is number one Fast Moving Consumer Goods (FMCG) Company in India.